2013
DOI: 10.1177/1479164113510923
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inhibitors of the Wnt signalling pathway (sclerostin and Dickkopf-1) and carotid intima-media thickness in postmenopausal women with type 2 diabetes mellitus

Abstract: The aim of the study was to investigate the association of the extracellular inhibitors of Wnt/β-catenin signalling sclerostin and Dickkopf-1 (Dkk-1) with carotid intima-media thickness (CIMT) in type 2 diabetes mellitus (T2DM). We performed a cross-sectional study including 40 T2DM postmenopausal women and 40 healthy controls. CIMT was measured by B-mode ultrasound. Serum sclerostin and Dkk-1 were measured by solid-phase enzyme-linked immunosorbent assay (ELISA). Serum sclerostin and Dkk-1 concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 30 publications
6
48
1
5
Order By: Relevance
“…In agreement with this study, comparable sclerostin values between patients and controls, were also observed in two adult T1DM studies , whereas one study demonstrated higher sclerostin values in adult T1DM patients. In adult T2DM studies sclerostin levels were constantly reported higher in patients than controls . In these studies sclerostin was higher in men , positively associated with chronological age and disease duration , while positive association or absent association with BMI was found.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with this study, comparable sclerostin values between patients and controls, were also observed in two adult T1DM studies , whereas one study demonstrated higher sclerostin values in adult T1DM patients. In adult T2DM studies sclerostin levels were constantly reported higher in patients than controls . In these studies sclerostin was higher in men , positively associated with chronological age and disease duration , while positive association or absent association with BMI was found.…”
Section: Discussionsupporting
confidence: 89%
“…These data may account for an increased cardiovascular risk in men in comparison with women with T1DM. In addition, our results seem to be in line with a recent report showing that, in T2DM postmenopausal women, sclerostin was negatively associated with IMT, and was an independent predictor of IMT in multivariate linear regression analysis (40). Taken together with our findings, these evidences suggest that sclerostin may be involved in the delay of atherosclerosis progression.…”
Section: Clinical Studysupporting
confidence: 82%
“…16 In a cross-sectional study conducted in patients with T2D, higher levels of SC were observed in subjects with concomitant atherosclerotic disease compared with subjects without atherosclerotic lesions. 12 In contrast, a negative correlation was observed between serum SC and carotid intima-media thickness in women with T2D 17 and in Afro-American men with T2D and calcified atherosclerotic plaques. 18 These findings suggest a possible role of SC in the development of atherosclerosis in patients with T2D, although the specific function of SC remains to be elucidated.…”
Section: Highermentioning
confidence: 90%